2023
DOI: 10.1002/pds.5599
|View full text |Cite
|
Sign up to set email alerts
|

Tying research question and analytical strategy when variables are affected by medication use

Abstract: Ill‐defined research questions could be particularly problematic in an epidemiological setting where measurements fluctuate over time due to intercurrent events, such as medication use. When a research question fails to specify how medication use should be handled methodologically, arbitrary decisions may be made during the analysis phase, which likely leads to a mismatch between the intended question and the performed analysis. The mismatch can result in vastly different or meaningless interpretations of esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…The validity of the method used for each variable was evaluated in relationship to the research aim and whether the affected variable is an exposure, an outcome, or a confounder. The assessment on whether the methods used are in general valid or invalid was based on recommendations from previous methodological studies 2–6,10,11,17–26 . For example, restricting the study population to non‐medication users was considered valid when the exposure or a confounder is affected by medication use regardless of whether the research aim is in the values as observed or if untreated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The validity of the method used for each variable was evaluated in relationship to the research aim and whether the affected variable is an exposure, an outcome, or a confounder. The assessment on whether the methods used are in general valid or invalid was based on recommendations from previous methodological studies 2–6,10,11,17–26 . For example, restricting the study population to non‐medication users was considered valid when the exposure or a confounder is affected by medication use regardless of whether the research aim is in the values as observed or if untreated.…”
Section: Methodsmentioning
confidence: 99%
“…The assessment on whether the methods used are in general valid or invalid was based on recommendations from previous methodological studies. [2][3][4][5][6]10,11,[17][18][19][20][21][22][23][24][25][26] For example, restricting the study population to non-medication users was considered valid when the exposure or a confounder is affected by medication use regardless of whether the research aim is in the values as observed or if untreated. This is because the restriction on a proxy variable of the Exceed 100% when added up, because more than one analysis was performed in some studies.…”
Section: Step IImentioning
confidence: 99%
See 2 more Smart Citations
“…Another limitation is that we did not explicate how an estimand can inform the choice of study design and analytical approach. We refer to existing papers on this topic, 29,33,41,[45][46][47] particularly to explanations about aligning estimands to estimators in randomized trials. 38,48 An increasingly popular methodological approach is the target trial emulation framework.…”
Section: As-needed Treatmentsmentioning
confidence: 99%